PENGARUH FAKTOR RESILIENSI TERHADAP KETAHANAN INDIVIDU SETELAH KEJADIAN TRAUMATIK - Utami, Prabawati Dwi; Sa'adah, Nurus (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This study aims to understand the importance of reflecting on and deeply understanding traumatic events in building resilience. Using qualitative methods, this study involved seven respondents aged 18-25 years who experienced traumatic events, with data collection methods in the form of structured interviews and observations. The results showed that resilience plays an important role in helping respondents to recover after experiencing traumatic events, with several factors such as social support, emotional intelligence, gratitude, optimism, self-acceptance, and learning from experience. Some respondents showed positive changes and attitudinal changes that encouraged them to rise and thrive. Social support, especially from family and being able to manage emotions and take lessons from traumatic experiences are key in building resilience. This study can contribute to understanding the processes and factors that support a person in overcoming crisis and trauma and developing psychological resilience.